Application of composite materials in sports optics - Kupčák, Radim; Zouhar, Jan (Manufacturing Technology Journal, 2020)
CFRP (Carbon Fiber Reinforced Polymers) are often used when designing parts that need to be stiff, light and thermally stable. These benefits are a big motivation to use CFRP in many applications, one of them could be sports optics. However, optical devices require precise dimensions with tight tolerances for the opti-cal assembly to work correctly. In order to determine if CFRP could be a suitable material of choice for sports optics a simplified body of binoculars was designed. The main purpose of this prototype was to prove the possibility of using CFRP in binoculars. The tubular body was manufactured by prepreg lay-up into a 3D printed mold, followed by curing in an autoclave. After the prototype was manufactured 3D measurements of the tube using 3D scanner GOM ATOS were made. As expected, shrinkage of the mold and the epoxy resin in the matrix of CFRP caused minor deformations. However, if the shape of the cured part remains unchanged during conditions similar to the general use of binoculars, then the initial deformations happening during manufacturing could be accoun-ted for when designing the part. Other than the carbon part itself, the bond between metal and composite components is another potential point of failure in terms of desired precision. Because of that measurements and tests of concentricity of ad-hesive joints are being currently performed. The results of these tests and others that will follow will indicate if composite materials could be used as a structural material for sports optics.
Keywords: carbon fiber; sports optics; prepreg; composite materials; 3D scan